KODE SEMIOTIKA ROLAND BARTHES DALAM CERPEN PELAJARAN MENGARANG KARYA SENO GUMIRA AJIDARMA DAN THE STORY OF AN HOUR KARYA KATE CHOPIN - Kevin Kournikova Budiman (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This research aims to describe and compare the application of Barthes' five codes in the short stories “Pelajaran Mengarang” and “The Story of an Hour.” This study is a descriptive qualitative research with a semiotic theoretical framework of Roland Barthes and comparative literature studies as the analytical approach. The data collection technique used is document study using the short story “Pelajaran Mengarang” by Seno Gumira Ajidarma, the short story “The Story of an Hour” by Kate Chopin, and relevant literature sources. The data analysis techniques include reading and understanding the content of the short stories, identifying data, classifying data based on Barthes' five codes, analyzing and describing the data, comparing the application of Barthes' five codes in the two short stories, and drawing conclusions. The analysis results show that both short stories build meaning through narrative puzzles, connotative signs, symbolic opposition, sequences of actions, and social values. Barthes' five codes semiotic theory reveals social criticism through the inner experiences of female characters in both short stories. This research contributes to semiotic studies, comparative literature studies, and enhances the understanding of Barthes' five codes in literary works.